Regional lithium prescription rates and recurrence in bipolar disorder - Sköld, M; Rolstad, S; Joas, E; Goodwin, GM (SpringerOpen, 2021)
Background: Lithium is the best documented maintenance treatment in bipolar disorder, but its use varies considerably across and within countries. It is not known whether regional differences in lithium prescription rates translate to differing regional outcomes.